Kesenian Sikambang dalam Kajian Resepsi Budaya Masyarakat Pesisir Kota Sibolga - Melayu, Juliarni; Yusril, Yusril (Melayu Arts and Performance Journal, 2023)
Sikambang Art Research in the Study of Cultural Reception of the Coastal Communities of Sibolga City with the aim of knowing the opinions of the Sibolga coastal communities about their own Sikambang Art culture, what causes Sikambang art on the coast of Sibolga City to be underdeveloped, and the function of Sikambang Arts in Sibolga coastal communities. However, this Sikambang art is still found on the coast of Sibolga City. This research is expected to increase the interest of young people in Sibolga City, because there are also few other writings that talk about the art of Sikambang. Indeed, there are some writings, but they do not really lead to public opinion. The research method used is descriptive qualitative which includes several aspects, namely observation, interviews, documentation, data analysis, with data reduction, data presentation, data verification and literature study. The population in this study are Sikambang art artists who are still active on the coast of Sibolga City and the sample of this study is the coastal community of Sibolga City as connoisseurs of Sikambang art performances. The research is written with the survey results in accordance with the facts